Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Disability studies after the ontological turn: a return to the material world and material bodies without a return to essentialism - Feely, Michael (Disability & Society, 2016)
Over recent decades, poststructuralist theories have allowed critical disability scholars to challenge essentialist understandings of the human species and to contest discourses which divide humans into ‘normal’/‘impaired’ subjects with respect to a wide – and ever expanding – range of corporeal and cognitive traits. For critics, however, these theories are deeply flawed. By focusing primarily on language, poststructuralism shifts our critical attention away from the often harsh material realities of life for disabled people. This has led some to turn to critical realism and to effectively re-essentialise impairment. In this article, I wish to consider an alternative approach. I suggest that the recent ‘ontological turn’ in social theory has seen the emergence of new-materialist approaches – including Deleuze and Guattari’s ontology of assemblage and methodology of assemblage analysis – which allow us to consider disability as a material phenomenon without a return to essentialism.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; corps; cours; discipline; féminisme matérialiste; histoire et politique; humaines; ontologie; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; thématiques; études critiques du handicap

Manifestly Haraway - Haraway, Donna Jeanne (University of Minnesota Press, 2016)
"Electrifying, provocative, and controversial when first published thirty years ago, Donna Haraway's "Cyborg Manifesto" is even more relevant today, when the divisions that she so eloquently challenges–of human and machine but also of gender, class, race, ethnicity, sexuality, and location–are increasingly complex. The subsequent "Companion Species Manifesto," which further questions the human-nonhuman disjunction, is no less urgently needed in our time of environmental crisis and profound polarization. Manifestly Haraway brings together these momentous manifestos to expose the continuity and ramifying force of Haraway's thought, whose significance emerges with engaging immediacy in a sustained conversation between the author and her long-term friend and colleague Cary Wolfe. Reading cyborgs and companion species through and with each other, Haraway and Wolfe join in a wide-ranging exchange on the history and meaning of the manifestos in the context of biopolitics, feminism, Marxism, human-nonhuman relationships, making kin, literary tropes, material semiotics, the negative way of knowing, secular Catholicism, and more. The conversation ends by revealing the early stages of Haraway's "Chthulucene Manifesto," in tension with the teleologies of the doleful Anthropocene and the exterminationist Capitalocene. Deeply dedicated to a diverse and robust earthly flourishing, Manifestly Haraway promises to reignite needed discussion in and out of the academy about biologies, technologies, histories, and still possible futures."– Provided by publisher.
Keywords: LGBTQIA2+; animaux de compagnie; approches et analyses; chien; corps; cours; cyberféminisme; cyborg; discipline; discours dominant; identités LGBTQIA2+; lit4700; philosophie; point de vue situé; premier cycle; relations humains/animaux; ressource en ligne; sciences humaines; systèmes d'oppressions; technologie; thématiques

Des sexes innombrables: le genre à l'épreuve de la biologie - Hoquet, Thierry (Éditions du Seuil, 2016)
Combient y-at-il de sexes? "Deux!", répond l'opinion. "Deux" répond la science. Heureuse concordance : c'est donc que l'opinion a raison, conclura-t-on. Mais est-on si certain que l'opinion et la science disent, sur la question du sexe, la même chose? Quand l'opinion affirme qu'il y a deux sexes, elle soutient qu'il existe, dans chaque espèce, deux types d'individus et seulement deux. Il y aurait alors le masculin et le féminin. Mais quand la science avance qu'il y a deux sexes, que vise-t-elle ? Quelle est, pour un biologiste, la signification des termes "mâle" et "femelle" ? En tentant de compter les sexes, on doit bientôt se risquer à distinguer le normal du pathologique.
Section: 1 vol. (249 p.) : ill., couv. ill. en coul. ; 21 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; discipline; europe; france; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe biologique; sexisme; sexualité; systèmes d'oppressions; thématiques

Feminism is queer: the intimate connection between queer and feminist theory - Marinucci, Mimi (Zed Books, 2016)
Feminism is Queer is an introduction to the intimately related disciplines of gender and queer theory. While guiding the reader through complex theory, the author develops the original position of "queer feminism, " which presents queer theory as continuous with feminist theory. While there have been significant conceptual tensions between second wave feminism and traditional lesbian and gay studies, queer theory offers a paradigm for understanding gender, sex, and sexuality that avoids the conflict in order to develop solidarity among those interested in feminist theory and those interested in lesbian and gay rights. This accessible and comprehensive textbook carefully explains nuanced theoretical terminology and includes extensive suggested further reading to provide the reader with a full andthorough understanding of both disciplines.–Publisher information.
Section: xxiii, 200 pages : illustrations ; 23 cm
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; militance; philosophie; premier cycle; queer; sciences humaines; soc2014; thématiques

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques